Strategi Pengembangan Pariwisata Berkelanjutan Gurun Pasir Telaga Biru Pulau Bintan Era New Normal - Yuliska, Fitria; Azizah, Nur; Pikri, Insanul (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2024)
The research was conducted in the Telaga Biru Desert, Bintan Regency, Riau Archipelago. The purpose of this research is to explore the tourism potential of the Telaga Biru Desert ecotourism destination and collaborative management that can be applied as an effort to develop a sustainable tourism area. Gurun Pasir Telaga Biru is part of an industrial area owned by PT Surya Bangun Pertiwi (SBP) with a land reserve of 4,000 hectares. Telaga Biru Desert has an area of 50 hectares which is planned as an industrial area green belt because of its location close to the Bintan airport. This research uses mixed methods, namely analysis from observations and interviews supported by quantitative data using Maple 2017 to understand the economic value and willingness of tourists to pay when visiting the tourist destination of the Telaga Biru Desert Desert. PT Surya Bangun Pertiwi (SBP) can use the Total Economic Value results as a data review to decide whether to keep the area as idle land or develop it as a nature-based tourism destination. The total economic value of the Telaga Biru Desert is IDR 493,950,214,550 per year, which means the economic value is IDR 862,290 per meter2. This figure is relatively high when compared to small businesses in providing a place with adequate facilities. Tourists can explore tourist areas with various interesting spots and try various kinds of rides provided. This destination will be more valuable if it carries out good collaborative management with more adequate infrastructure and can encourage the growth of MSMEs, education and the social community of the local community.